Management of an outbreak of brucellosis in a multiple species ruminant farm in Malaysia - Bitrus, Asinamai Athliamai; Abba, Yusuf; Abdullah, Faez Firdaus Jesse; Che' Amat, Azlan; Mazlan, Mazlina; Peter, Innocent Damudu; Hambali, Idris Umar; Haron, Abd Wahid; Mohd Lila, Mohd Azmi (Universiti Putra Malaysia Press, 2018)
This case report describes the management of an outbreak of brucellosis in a mixed ruminant farm in Selangor, central region of Peninsular Malaysia. Two cows with a history of abortion and endometritis were presented to the University Veterinary Hospital, Faculty of Veterinary Medicine, Universiti Putra Malaysia. Based on the history, physical examination and results of Rose Bengal Plate Test (RBPT), brucellosis was highly suspected. This led to the screening of all the animals (n = 384) in the affected farm. The Rose Bengal Plate Test (RBPT) revealed that 23 cattle were positive, while no agglutination was observed in goats and deer. A confirmatory test was performed on all the (n = 384) animals using the complement fixation test (CFT) and the results showed that two (2) cows and five (5) deer tested positive. The CFT positive animals were culled. Preventive steps were then taken where the remaining cattle in the herd were vaccinated once using the RB51 vaccine, while the deer and goats were not vaccinated. All animals in the herd were also recommended to be subjected for blood sampling every 4 months and the serum samples to be tested using competitive ELISA to distinguish between serological responses due to vaccination from infection. To overcome outbreak scenario of brucellosis in a farm, a prompt action and a concerted team work among relevant stakeholders are crucial to curb the situation.